Analisis Tax Amnesty Terhadap Penyerapan Dana Repratisi (Studi Kasus Pada Bank Syariah Indonesia) - Khairani Nisa; Nur Ahmadi Bu Rahmani; Muhammad Syahbudi (AGHNIYA : Jurnal Ekonomi Islam, 2023)
This study aims to determine the differences in the financial performance of Bank Syariah Indonesia, which became a tax amnesty perception bank between before and after the existence of tax amnesty in Indonesia. This type of research is quantitative research using financial ratio report data by opening the official website from 3 years before the tax amnesty, and 5 years after the tax amnesty was implemented. The analysis used in this study is statistical software that can explain the difference in financial performance before and after the tax amnesty from one variable, namely CAR in Indonesian Islamic banks as well as knowing the effect on financial ratios before and after the implementation of the tax amnesty. The results of the study show that there is no real difference in financial ratios both before and after the implementation of the tax amnesty. And the CAR ratio at Bank Syariah Indonesia does not experience a significant influence on the situation and condition of the tax amnesty at Bank Syariah Indonesia, which is a perception bank.